TINJAUAN HUKUM LINGKUNGAN TERHADAP PERLINDUNGAN DAN PENGELOLAAN KEANEKARAGAMAN HAYATI - Asram AT Jadda (Madani Legal Review, 2019)
This research discusses the protection and management of biodiversity in environmental law perspective. Indonesia has a large biodiversity which needs to be managed and protected. Indonesia has enacted laws and regulations on biodiversity, but they are still weakly and less effectively implemented. Furthermore, it is a fact that regulations stipulated by the government or certain sectors do not still accommodate interests of all parties. Legal issues examined here is whether Act No. 32 of 2009 on the Protection and Management of the Environment has protected biodiversity in Indonesia and how is the implementation of policies in protecting biodiversity during this time. The research results show that Act No. 32 of 2009 on the Protection and Management of the Environment has protected the biodiversity in Indonesia. Implementation of policies about the protection and management of biodiversity during this time can be viewed from the relationship of policy between the government and the regional government, such as the authority and institutions to manage and protect the environment, including instruments to manage biodiversity